2006
DOI: 10.5194/acp-6-3257-2006
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol chemical and optical properties over the Paris area within ESQUIF project

Abstract: Abstract. Aerosol chemical and optical properties are extensively investigated for the first time over the Paris Basin in July 2000 within the ESQUIF project. The measurement campaign offers an exceptional framework to evaluate the performances of the chemistry-transport model CHIMERE in simulating concentrations of gaseous and aerosol pollutants, as well as the aerosol-size distribution and composition in polluted urban environments against ground-based and airborne measurements. A detailed comparison of meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 48 publications
(69 reference statements)
0
28
1
Order By: Relevance
“…Time-limited information in the chemical composition of fine aerosols in Paris have been recently reported by Gros et al (2007) but for a site impacted by traffic which may not be fully representative for the composition and levels of aerosols in the Paris urban background atmosphere. Modelling studies over Paris have been reported in literature but concerned mainly PM with A.D. <10 µm (PM 10 ) or total suspended matter size fractions (Bessagnet et al, 2005;Hodzic et al, 2006). As a result, chemical composition of PM 2.5 over the region of Paris remains poorly documented and regional model simulating PM 2.5 concentrations and composition over this region poorly constrained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time-limited information in the chemical composition of fine aerosols in Paris have been recently reported by Gros et al (2007) but for a site impacted by traffic which may not be fully representative for the composition and levels of aerosols in the Paris urban background atmosphere. Modelling studies over Paris have been reported in literature but concerned mainly PM with A.D. <10 µm (PM 10 ) or total suspended matter size fractions (Bessagnet et al, 2005;Hodzic et al, 2006). As a result, chemical composition of PM 2.5 over the region of Paris remains poorly documented and regional model simulating PM 2.5 concentrations and composition over this region poorly constrained.…”
Section: Introductionmentioning
confidence: 99%
“…The model has been also extensively used to simulate gas phase pollution levels over the Paris region (e.g., Vautard et al, 2001;Beekmann et al, 2003;Derognat et al, 2003;Deguillaume et al, 2007 and, and on several occasions particulate matter (e.g. Bessagnet, 2005;Hodzic et al, 2006).…”
Section: Model Descriptionmentioning
confidence: 99%
“…Measurements during MILAGRO (e.g. Kleinman et al, 2008;de Gouw et al, 2009) and other field campaigns worldwide (de Gouw et al, 2005;Simpson et al, 2007;Hodzic et al, 2006;Zhang et al, 2007) have indicated that, as a result of secondary organic aerosol (SOA) formation processes, organic aerosol mass is much higher than one would expect from primary emissions and dispersion. However, the understanding of how anthropogenic and biogenic precursors contribute to SOA formation is far from complete.…”
Section: Introductionmentioning
confidence: 99%
“…Several urban plume studies have been carried out within comprehensive but short field campaigns in large cities (> 1 million people), e.g. Mexico City (Doran et al, 2007;Hodzic et al, 2009;Tsimpidi et al, 2010), Tampa (Nolte et al, 2008), Paris (Hodzic et al, 2006) and Copenhagen (Wang et al, 2010), while very few, if any, such studies have been carried out in small to midsize cities (< 1 million people). Still, about 60% of the urban population of the world live in small to midsize cities (Population Div.…”
Section: Introductionmentioning
confidence: 99%